2017
DOI: 10.18632/oncotarget.22940
|View full text |Cite
|
Sign up to set email alerts
|

c-Myb and C/EBPβ regulate OPN and other senescence-associated secretory phenotype factors

Abstract: Tumorigenesis results from the convergence of cell autonomous mutations and corresponding stromal changes that promote tumor cell growth. Senescent cells, which secrete a plethora of pro-tumorigenic factors termed the senescence-associated secretory phenotype (SASP), play an important role in tumor formation. Investigation into SASP regulation revealed that many but not all SASP factors are subject to NF-kB and p38MAPK regulation. However, many pro-tumorigenic SASP factors, including osteopontin (OPN), are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Specifically, the accumulation of senescent hepatocytes has been shown to promote progression (Aravinthan & Alexander, 2016). Previous work has described osteopontin (OPN) as a senescence‐associated secretory phenotype (SASP) factor (Flanagan et al., 2017; Pazolli et al., 2009). Although senescence‐associated cell cycle exit likely evolved as an antitumor mechanism, SASP contains both anti‐ and pro‐tumorigenic potential (Lau & David, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the accumulation of senescent hepatocytes has been shown to promote progression (Aravinthan & Alexander, 2016). Previous work has described osteopontin (OPN) as a senescence‐associated secretory phenotype (SASP) factor (Flanagan et al., 2017; Pazolli et al., 2009). Although senescence‐associated cell cycle exit likely evolved as an antitumor mechanism, SASP contains both anti‐ and pro‐tumorigenic potential (Lau & David, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its role as a metabolic modulator, it controls the fate of acetyl‐CoA in liver (Nunez‐Garcia et al., 2017; Nuñez‐Garcia et al., 2018) and rewires liver lipid metabolism after partial hepatectomy (Nuñez‐Garcia et al., 2018). OPN is considered a senescence‐associated secretory phenotype (SASP) factor (Flanagan et al., 2017; Pazolli et al., 2009). SASP factors are mainly cytokines, chemokines, and proteases with autocrine and paracrine effects that affect the neighboring cells and are able to induce senescence (Coppé, Desprez, Krtolica, & Campisi, 2010; Malaquin, Martinez, & Rodier, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although former studies suggested the presence of C/EBP binding sites in the promoters of SASP factors, particularly a subset of CXCR2 ligands including IL-6, IL-8, GROα/β/γ (CXCL1/2/3), ENA-78 (CXCL5), and NAP2 (CXCL7) 46 , we extended the range of C/EBP-regulated SASP factors by adding SPINK1. Interestingly, a recent study reported that c-Myb and C/EBP co-regulate osteopontin (OPN) and many other SASP factors 50 , further suggesting the regulatory complexity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SASP forms a stable positive loop via autocrine and paracrine mechanism, which leads to signal amplification (Herranz and Gil, 2018). The expression of the majority of SASP is regulated by nuclear factor κ-B (NF-κB), CCAT/enhancer binding protein-β (C/ EBP-β), p38 mitogen-activated protein kinase (MAPK) (Flanagan et al, 2018). DNA damage and oxidative stress activate NF-κB signaling, leading to overexpression of downstream SASP (Taniguchi and Karin, 2018;Wei and Ji, 2018).…”
Section: Saspmentioning
confidence: 99%